PENGARUH UKURAN PERUSAHAAN DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN MANAJEMEN LABA SEBAGAI VARIABEL INTERVENING - Permatasari, Susanti; Asyik, Nur Fadjrih (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is aimed to examine the influence of firm size and profitability of firm value to the earningmanagement as the intervening variable. The sampling method has been carried out by using purposivesampling method and 39 companies have been obtained as samples. The data have been obtained from thefinancial statements of companies which are listed in the Indonesia Stock Exchange in 2012-2014 periods. Themethod analysis is quantitative which has been carried out by using classic assumption test and statisticalanalysis i.e. path analysis which has been performed by using two structural equations in order to measure thedirect and the indirect influence among the independent variables to the dependent variable by using interveningvariable. The result of analysis shows that firm size and profitability do not have any significant influence bothsimultaneous and partial to the earning management which can be seen from the structural equation 1.Meanwhile the structural equations 2 shows that firm size, profitability and earnings management havesignificant influence both simultaneous and partial to the firm value.Keywords: Firm size, profitability, earning management and the value of the company.